KAJIAN TERHADAP HUBUNGAN ANTARA PIDANA MATI DENGAN HAK ASASI MANUSIA - Estri Banjaransari; Yesika Rahman; Belinda Ayu; Rifki Pebrianata (Universitas Stikubank, 2023)
This study aims to find out the study of the relationship between capital punishment and human rights. The type of research used is a systematic literature review, namely the study of related journals, articles, laws, and books. The results of this study indicate that the death penalty in Indonesia still experiences several mistakes that lead to violations of human rights, so capital punishment is needed as an alternative punishment.